١٩٦٧اﻟﺪﻋﻢ اﻟﻠﯿﺒﻲ ﻟﻤﺼﺮ ﻓﻲ ﺣﺮب ﺣﺰﯾﺮان )ﺑﺤﺚ ﻣﺴﺘﻞ ﻣﻦ رﺳﺎﻟﺔ ﻣﺎﺟﺴﺘﯿﺮ( (Journal of the College of Education for Women, 2019)
The Libyan-Egyptian relations since 1952 to 1969, which studies two neighboring states ,and the geographical proximity has an effect in documenting and cementing the relationship between the two states. They share 1094 m long borders. That was reflected on the kind of relationship the two countries has shares. The Libyan-Egyptian relationship is not a superficial one, as the two countries have shared borders. What lies between them is a mixture of geography and human. It is an undying history. Our choice of the topic is limited to the period 1952 the beginning of the LibyanEgyptian. The revolution of 23rd July 1952 in Egypt and the declaration of republic there. For Libya, it was the monarchy in 1969 with the September 1 revolution. The great role of Egypt in supporting the Libyan people in its struggle against the Italian occupation. Egypt was the first country to aid the mujahedeen in Libya. That was headed by Amir Omar Touson. In spite of the seize over the Egyptian borders, the struggle over the line of Omar AlMukhtar. Italy realized the importance of Al-Jaghbob oasis in the strife, and it made all it could to help Britain amend the borders between the two countries to include the Oasis in the Libyan borders, that what had happened in 1925. Egypt has also played a role in the international field until Libya was independent in 1951. The research tackles the relationship after the Libyan during the 1967War, The official and popular attitude was clear. The June setback is regarded as one of the gravest events, in the Arabic and international arena, which formed the history of the Arabic Homeland.